Heart Transplantation in a Fontan Patient Using a Hepatitis C-Positive Donor. Issue 4 (July 2019) - Menachem, Jonathan N.; Bichell, David P.; Frischhertz, Benjamin; Shah, Ashish S.; Schlendorf, Kelly
A 38-year-old female with tricuspid atresia and normally related great arteries, initially palliated with Björk modified Fontan, and ultimately converted to extracardiac conduit Fontan, with a history of ventricular tachycardia and hepatitis C virus (HCV) treated with sofosbuvir/ledipasvir, was referred to our center for consideration of combined heart and liver transplantation. The patient's blood group was O with panel reactive antibodies of 52%. She consented to consideration of HCV-positive donors. Fifteen days later, an HCV-positive donor was identified, and she underwent heart transplantation with pulmonary artery reconstruction performed jointly by adult and pediatric transplant surgeons. To our knowledge, this the first time an HCV-positive donor heart has been to transplant an adult with congenital heart disease.